Cardiac responses to exercise in child distance runners - Rowland, T.; Goff, D.; Popowski, B.; DeLuca, P.; Ferrone, L. (International Journal of Sports Medicine, 1998)
Cardiovascular responses to exercise in trained endurance child athletes have been largely unexplored. Doppler echocardiography was utilized to compare cardiac variables during progressive upright cycle exercise to exhaustion in trained male prepubertal distance runners (n = 8) and untrained control boys (n = 14). Athletes demonstrated a greater maximal stroke index and cardiac index. Stroke volume rose progressively with increasing workloads in the runners but remained stable beyond low intensities in the non-athletes. No significant differences in stroke volume were observed between the two groups at rest. This contrasts with the greater resting stroke volumes typically seen in adult endurance athletes compared to non-athletes. Likewise, values for maximal stroke index were less in the child runners than those typically seen in trained adults. This study demonstrated that the stroke volume response to exercise differs in boy runners compared to non-athletes. The findings also suggest quantitative differences in such responses between prepubertal and young adult athletes.